Literature Review: Risk-Based Audit Approach in Operational Auditing in Indonesian Islamic Banking Companies - Maisyarah, Renny; Syari, Meilya Evita (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research is a literature review that discusses the risk-based audit approach in operational audits in Islamic banking institutions in Indonesia. This audit approach emphasizes the identification, assessment, and management of risks as the basis for planning and executing audits, with the aim of improving the effectiveness and efficiency of operational supervision. Through an analysis of relevant academic literature, regulations, and industry practices, this study examines how risk-based auditing approaches are applied in Indonesia's Islamic banking sector, as well as the challenges and opportunities faced in its implementation. The results of the review show that although this approach has great potential in improving audit quality and compliance with sharia principles, its implementation still faces obstacles in the form of limited auditor resources, understanding of sharia risk management, and information system infrastructure. This study provides important insights for auditors, regulators, and management of Islamic banks in strengthening governance and internal controls through the implementation of effective risk-based audits.